Haematological Indices and Fertility Potential of Rabbits Receiving Camels Foot (Piliostigma thonningii) Essential Oil Supplemented Diet - Emmanuel Anaso; Olurotimi Olafadehan; Ijeoma C. Chibuogwu; Ayoola J. Shoyombo; Samuel Mailafia; Joy N. Anaso; Emeka Solomon Fidelis (Turkish Journal of Agriculture: Food Science and Technology, 2024)
The current study aimed to evaluate Piliostigma thonningii seeds-derived essential oil (PTO) effect on hematological and reproductive parameters in rabbits. Three groups consisting of 15 animals each were randomly assigned and with an average initial body weight (BW) of 262.89 ± 22.36 g in a fully randomised experimental design. Group 1 received the control diet, while for groups 2 and 3 the basal control diet was supplemented with 2 mL PTO/kg diet and 4 mL PTO/kg diet, respectively. At the end of the experiment, blood samples were collected and the blood was analysed using the ABACUS ROSS haematology analyser. The results indicated significant differences in rabbits receiving PTO supplemented feed, namely; Packed cell volume, red blood cells, white blood cells, mean corpuscular haemoglobin concentration, neutrophil increased (P<0.05) with increasing level of PEO supplementation. Mean corpuscular volume and haemoglobin, lymphocyte, monocyte and platelet were higher (P<0.05) in T2 and T3 than in T1. Neutrophil/lymphocyte ratio was higher (P<0.05) in T3 than T1 with T2 being intermediate (P>0.05) between T1 and T3. Semen volume, concentration and motility were higher (P<0.05) in T2 and T3 than in T1. While semen abnormalities and bucks’ reaction time to does (libido) were greater (P<0.05) in T1 than in T2 and T3, Live dead ratio was higher (P<0.05) in T3 relative to T1 while T2 was intermediate between T1 and T3 (P>0.05). semen color and pH were not affected (P>0.05) by treatments. It was therefore concluded that P. thonningii essential oil supplementation enhanced both haematological and fertility potential of the experimental rabbits.